A Stable Silene Substituted by Strong π‐Donors at the Silicon Center1. Issue 41 (2nd September 2013) - Nakata, Norio; Rodriguez, Ricardo; Troadec, Thibault; Saffon‐Merceron, Nathalie; Sotiropoulos, Jean‐Marc; Baceiredo, Antoine; Kato, Tsuyoshi
<x xml:space="preserve">Abstract</x> Keen to donate: A stable and isolable silene with two π‐donating groups on the silicon center has been synthesized. This silicon‐substituted silene shows totally different π‐substituent effects compared to those of related carbon‐substituted silenes, and it presents intrinsic silene properties with an enhanced electron‐donating character, making it an excellent ligand for transition metals.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>